IDENTIFIKASI DAN PERANCANGAN SISTEM PENGELOLAAN DATA SUMBER DAYA AIR PROVINSI GORONTALO - Wahyono, Heru Dwi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2004)
Gorontalo Province as new agricultural base province in the autonomous effortsthrough the Agency for Water Resources Management has been collecting andmanaging all data of water resources. Good data management for water resources is needed to support agricultural and fishery base activity in this province. The identification of potential of the existing water resources is needed for computer base structural database management system design. The design of database system is used as reference for development of software for water resources database management. The developed software can be used as Decision Support System to help provincial management and useful for information system to find out the potential of all water resources in Gorontalo Province area. The output of this activity is software for managing water resources in Gorontalo Province.